2004
DOI: 10.1063/1.1640337
|View full text |Cite
|
Sign up to set email alerts
|

Sticking of CO to crystalline and amorphous ice surfaces

Abstract: We present results of classical trajectory calculations on the sticking of hyperthermal CO to the basal plane (0001) face of crystalline ice Ih and to the surface of amorphous ice Ia. The calculations were performed for normal incidence at a surface temperature Ts = 90 K for ice Ia, and at Ts = 90 and 150 K for ice Ih. For both surfaces, the sticking probability can be fitted to a simple exponentially decaying function of the incidence energy, Ei: Ps = 1.0e(-Ei(kJ/mol)/90(kJ/mol)) at Ts = 90 K. The energy tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
39
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 58 publications
6
39
0
Order By: Relevance
“…While nowadays there is a currently general agreement as regard the peak at 2152 cm −1 , present both in the apolar mixture and the hydrogenated ice surfaces, and assigned to CO adsorbed on dH sites through its carbon atom, the nature of the 2143 and 2139-2136 cm −1 peaks remains still controversial. Rather surprising, the 2152 cm −1 signal has not been found in any of the interstellar spectra (Collings et al 2003a;Al-Halabi et al 2004a) while signals around 2143 cm −1 appear as a prominent shoulder of the main peak as well as the redshifted features between 2139-2136 cm −1 . In the following, we will explore at the same level of accuracy many different configurations of the CO/H 2 O ice binary system and we will analyze the IR fingerprint for each of them.…”
Section: Brief Review Of Previous Studiesmentioning
confidence: 96%
“…While nowadays there is a currently general agreement as regard the peak at 2152 cm −1 , present both in the apolar mixture and the hydrogenated ice surfaces, and assigned to CO adsorbed on dH sites through its carbon atom, the nature of the 2143 and 2139-2136 cm −1 peaks remains still controversial. Rather surprising, the 2152 cm −1 signal has not been found in any of the interstellar spectra (Collings et al 2003a;Al-Halabi et al 2004a) while signals around 2143 cm −1 appear as a prominent shoulder of the main peak as well as the redshifted features between 2139-2136 cm −1 . In the following, we will explore at the same level of accuracy many different configurations of the CO/H 2 O ice binary system and we will analyze the IR fingerprint for each of them.…”
Section: Brief Review Of Previous Studiesmentioning
confidence: 96%
“…Analytic models can not provide the required degree of accuracy and for molecular dynamics simulations and specifically in a force-field context, the amount of studied systems remains small and far from general. H has been extensively studied [18][19][20][21][22] and CO has also received some attention 23,24 . We have not been able to find data for H 2 , apart from a PhD thesis chapter 25 .…”
Section: Introductionmentioning
confidence: 99%
“…[40][41][42][43] Starting from the normal hexagonal ice (I h ) crystalline ice configuration (containing 8 bilayers (BLs) (16 MLs) with 60 (30) molecules in each ML), the amorphous ice surface was set up at 10, 20, 60, or 90 K using the "fast quenching" method" [46][47][48] Further details can be found in our previous studies. [41][42][43] Since the resulting amorphous ice surface has a more irregular bonding structure than the crystalline ice surface, 41,47 assigning molecules to MLs is not straightforward. 43 In our most recent study 43 a new definition of ML (binning method 2) was tested and shown to be a more realistic way to assign molecules to MLs.…”
Section: B Amorphous Ice Surfacementioning
confidence: 99%